Mid-length Pedicle Screws in Posterior Instrumentation of Scoliosis - (:unkn) unknown (KOREAN SOC SPINE SURGERY, 2019)
Study Design: Prospective analysis of collected data. Purpose: We determine the need for the use of mid-length pedicle screws (screws with 2.5-mm long increments) during posterior spinal instrumentation. Overview of Literature: Many biomechanical studies have been performed showing that increasing the pedicle screw insertion depth provides an improved resistance to pullout, cyclic loading, and derotational forces, but no intermediate length screws were used. Methods: We prospectively evaluated 120 patients who received posterior segmental instrumentation for structural scoliosis. Preoperatively, 91.44-cm long cassette anteroposterior (AP), lateral, and AP bending radiographs and multiplanar computed tomography were performed in all patients routinely. We measured chord length to determine the maximum probable screw length of all vertebrae. All pedicle screws were attempted to be placed as long as possible. The main intention was at least to engage the subcortical bone of the anterior vertebral cortex. Especially in the apical region, the screws were attempted to be inserted bicortically. The length, level, region, and side of each screw were recorded. Screws with 5-mm increments were called standard length screws (SLS), and middle-sized screws with 2.5-mm increments were called mid-length screws (MLS). Results: Of 2,846 pedicle screws inserted, 1,575 (55.4%) were SLS and 1,271 (44.6%) were MLS, demonstrating a need for MLS in scoliosis surgery (p>0.05). The need for MLS increased significantly in the thoracic region, apical vertebrae, and convex side (p<0.05). Conclusions: If anterior cortex engagement or longer placement of pedicle screws is intended during scoliosis surgery, for safer placement, screws with 2.5-mm increments should be available in posterior instrumentation systems.
Keywords: Scoliosis; Chord length; Pedicle; Screw; Surgery; DEFORMED SPINE; THORACIC SPINE; PLACEMENT; VERTEBRAE; FIXATION; LUMBAR; THORACOLUMBAR; COMPLICATIONS; BIOMECHANICS; MORPHOLOGY